Cross-talk between the gut microbiota and monocyte-like macrophages mediates an inflammatory response to promote colitis-associated tumourigenesis. Issue 8 (29th October 2020) - Yang, Yunben; Li, Lili; Xu, Chunjing; Wang, Yunke; Wang, Zhen; Chen, Mengyao; Jiang, Zhou; Pan, Jun; Yang, Chenghui; Li, Xiaoqian; Song, Kai; Yan, Junfeng; et al.
Abstract : Objective: Macrophages are among the most abundant cells in the colon tumour microenvironment, and there is a close relationship among monocytes, macrophages and the gut microbiota. Alterations in the gut microbiota are involved in tumour development, but the underlying mechanisms remain unclear. We aim to elucidate the temporal changes in macrophage subsets and functions, and how these dynamics are regulated by microbial cues in the initiation of colitis-associated cancer. Design: A mouse model of colitis-associated tumourigenesis was established to determine macrophage dynamics. The role of monocyte-like macrophage (MLM) was confirmed by targeting its chemotaxis. The effects of the gut microbiota were assessed by antibiotic treatment and faecal microbiota transplantation. Results: A selective increase in MLMs was observed in the initial stages of colitis-associated cancer, with an enhanced secretion of inflammatory cytokines. MLM accumulation was regulated by CCL2 expression of colonic epithelial cells, which was influenced by bacteria-derived lipopolysaccharide (LPS). LPS further stimulated interleukin 1β production from MLMs, inducing interleukin-17-producing T-helper cell activation to promote inflammation. These observations were also supported by altered microbial composition associated with human colitis and colorectal cancer, evolving transcriptional signature and immune response during human colitis-associated tumourigenesis. Conclusions: The gut microbiota uses LPS as a trigger to regulate MLM accumulation in a chemokine-dependent manner and generate a precancerous inflammatory milieu to facilitate tumourigenesis.